PERILAKU TANGGAP KEBAKARAN PADA BANGUNAN KAMPUS: Studi Kasus: Kampus Universitas Brawijaya, Malang - Sufianto, Heru; Murti Nugroho, Agung; Aditama, M Satya (Talenta Publisher, 2017)
Fires in buildings have significant impact on communities both socially and economically. In education facilities, fire incidents may instantly wipe out valuable scientific resources that were collected in years. Fire authorities, practitioners and relevant bodies have been addressed this issue by focusing on technical engineering approaches and requirements, more than human behaviour aspect. This study seeks the importance of human behaviour as pre-active and re-active controls for protecting campus building from fires. Number of tall buildings in Brawijaya University have been investigated and a number of occupants have been filled up the online questionnaire during field survey. This study suggested the improvement fire safety awareness of occupants, meanwhile fire safety management should be introduced and implemented consistently across management system in the university.